Proposed use of in vivo x-ray fluorescence to investigate health impact of Gd in MRI contrast agents and Sr in diet. (29th March 2019) - Chettle, David R.; Lord, Michelle L.
Abstract : Introduction: In vivo x-ray fluorescence (XRF), along with in vivo neutron activation can be used to measure elemental content in living human subjects. Two examples of current interest will be presented. Gadolinium based contrast agents (GBCA) are widely used, because they greatly facilitate magnetic resonance imaging studies. Initially considered completely benign, it was found that these GBCAs could be damaging to people with compromised kidney function. More recently concern has been raised about possible impact on people with normal kidney function. We have been developing an xrf method to measure Gd in bone. Strontium is harmful to bone in excess. However, Sr supplement administered to people diagnosed with osteoporosis reduced fracture risk. Because there were cardiovascular side effects, this treatment has been withdrawn. Risk of hip fracture varies from country to country. It is highest in North America and two times lower in East Asian countries. We developed an xrf method to measure Sr in bone. In an early study of a convenience sample of Canadian residents, we found that people of East Asian origin had three times the level of Sr in bone as people of Caucasian origin. This gives rise to an hypothesis that modest levels of Sr, perhaps acquired through lifelong diet, could reduce the risk of osteoporosis. Materials and methods: Xrf requires a source of x-rays or (-rays, which can then excite x-rays that are characteristic of a particular element in a sample. A detector is placed to collect the scattered x-rays and (-rays from the sample. For Gd measurement, we use 88keV (-rays from a 109 Cd source and an array of four hyperpure germanium detectors. For Sr we use x-rays and (-rays from a 125 I source, with energies between 22 and 35keV. We use a Si(Li) detector. The effective radiation dose in each of these measurements is less than 1:Sv. This compares, for example to annual background radiation dose of ∼1600:Sv in Lisbon. Results: We measured Gd in tibia of 11 people who had previously received GBCA and 11 control subjects [1 ]. As a group, the exposed subjects had significantly higher bone Gd than the controls, although the difference was small. We made repeated measurements of bone Sr in ten female volunteers who had chosen to take Sr supplements [2 ]. Over periods of up to four years, their bone Sr increased dramatically. The increase varied from a factor of ten to a factor of one hundred between subjects. Discussion and conclusions: We should like to improve the precision of the bone Gd measurement. However, the present system is sufficient to begin to investigate retention and storage of Gd for different GBCAs and in different types of subjects. The dramatic increase in bone Sr following supplementation raises the possibility that providing Sr to people already suffering from osteoporosis is too much, too quickly, too late and that a lifelong dietary adjustment might be a healthier option.